2014
DOI: 10.4081/ijas.2014.3141
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Supplemental Natural Zeolite in Broiler Chickens Subjected to Dietary Calcium Deficiency

Abstract: Natural zeolite, or sodium aluminosilicate, influences calcium (Ca) and phosphorus (P) utilisation in chicks. A 2×2 factorial arrangement of treatments was used to investigate the effect of dietary Ca (recommended and below recommended levels) and zeolite (0 and 0.8%) on growth, plasma, tibia and faeces in chickens from 1 to 42 days of age. Zeolite supplementation did not affect overall body weight (BW) gain, feed intake (FI) or feed conversion ratio (FCR) of broiler chickens (P>0.05). Overall mortality of zeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…On the other hand, zeolite is expected to increase the production of epithelial cells in broilers [17] and cause intestinal villus hypertrophy and epithelial cell activity in ducks [6] which could enhance nutritional absorption and digestion. This study agreed with [18][19][20]6,21], but disagreed with some studies finding [22,23,5].…”
Section: Resultssupporting
confidence: 51%
“…On the other hand, zeolite is expected to increase the production of epithelial cells in broilers [17] and cause intestinal villus hypertrophy and epithelial cell activity in ducks [6] which could enhance nutritional absorption and digestion. This study agreed with [18][19][20]6,21], but disagreed with some studies finding [22,23,5].…”
Section: Resultssupporting
confidence: 51%
“…(2016) , who noted that no significant differences on broiler performance were observed among the dietary 0.5% to 1.0% silicon groups. Similarly, Bintas et al. (2014) also reported that a dietary 0.8% silicon-based supplement did not significantly affect the overall body weight gain, feed intake, or feed conversion ratio of broiler chickens.…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, ZC restored the activity of antioxidant enzymes in murine models intoxicated with fluorides [76]. In chickens receiving daily ZC in food, antioxidant capacity was increased by reducing the free radical content of intestinal nitric oxide and increasing the activity of GSH, catalase and SOD enzymes [77,78,79]. Finally, the TMAZ (similar to PMA-ZC) has shown a particular antioxidant action in murine models of Alzheimer’s disease.…”
Section: Zeolite Clinoptilolite: a Multifaceted Rockmentioning
confidence: 99%